POSITIVE DISTRACTION AS A MEDIUM FOR MENTAL HEALTH REFRESHMENT FOR HOUSEWIVES IN SIDOARJO - Nastiti, Ratna Andriani; Hasya, Astrini Hadina; Musa, Hammam Bara Abu; Destiara, Cindi Cahya (Community Service Journal of Indonesia, 2025)
Mental health has become a prominent concern, particularly in the post-pandemic era. The aftermath of last year's lockdowns and the widespread adoption of work-from-home practices have led to increased feelings of monotony during indoor activities. This phenomenon is also evident among housewives, particularly within the Merpati Kehutanan Sidoarjo Housing Complex, where the repetitive nature of household chores can significantly impact quality of life. In response, community service initiatives introduced positive distraction activities aimed at revitalizing the mental well-being of housewives. These activities were based on the therapeutic benefits of art, specifically the collage technique. The program was strategically aligned with the routine activities of the housing complex, particularly the reuse of discarded cardboard. A total of 17 female participants actively engaged in the activity, ensuring its smooth implementation. The evaluation results indicated that artistic engagement serves as an effective form of mental therapy, contributing to psychological well-being and providing a refreshing experience for the participants.